Strategi Marketing Pedagang Angkringan Di Era New Normal - Edo Satria; Khairudin Khairudin (Sains: Jurnal Manajemen dan Bisnis, 2022)
MSMEs currently have an important role to developing the national economy, some MSMEs in Bandar Lampung are Angkringan, Angkringan in Bandar Lampung have experienced a lot of decline in sales due to Covid-19, Angkringan traders still do not understand the right marketing strategy during the pandemic, the purpose of this research to evaluate the marketing strategy used by Angkringan Om Napi. This research uses qualitative research with SWOT analysis. In accordance with the results of the analysis and discussion in previous chapters, namely the most appropriate defensive strategy to be applied to the formulation of the SWOT matrix strategy combination, the strategy with the highest priority order is Strength-Opportunity (3.64). Strength-Opportunity is a strategy that (strength taking advantage of existing opportunities). There are several main suggestions that Angkringan Om Napi can consider, namely increasing competitiveness, developing innovation, collaborating with partners and that are appropriate and mutually beneficial in the cooperation.